Convergence of developed countries : the example of Czech Republic and Norway since 1990 - Vrabcová, Eliška; Chalupecký, Petr; Krejčová, Nikola, 1974-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2023)
This bachelor thesis examines the real convergence between the Czech Republic and Norway from 1990 to 2020. It defines important concepts related to real convergence and utilizes beta convergence to test for real convergence, using GDP per capita in PPP. Additionally, fixed gross capital formation is added to the equation to analyze convergence. The study also employs human capital indicators, such as HDI and investment in education as a percentage of government expenditure, to evaluate convergence. The results are presented through tables and graphs. The study concludes that the Czech Republic has made progress in narrowing the economic gap with Norway, but convergence is still ongoing.
Vedoucí práce: Petr Chalupecký
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses